Day of the blizzard - Moskin, Marietta D.; Gammell, Stephen (New York : Coward, McCann & Geoghegan, 1997)
Eager to accomplish an errand for her sick mother, Katie braves one of New York City's severest snowstorms in history, the blizzard of 1888.
G4
Keywords: Blizzards -- Fiction; New York (N.Y.) -- Fiction